2022
DOI: 10.1186/s12871-022-01884-2
|View full text |Cite
|
Sign up to set email alerts
|

Practice of oxygen use in anesthesiology – a survey of the European Society of Anaesthesiology and Intensive Care

Abstract: Background Oxygen is one of the most commonly used drugs by anesthesiologists. The World Health Organization (WHO) gave recommendations regarding perioperative oxygen administration, but the practice of oxygen use in anesthesia, critical emergency, and intensive care medicine remains unclear. Methods We conducted an online survey among members of the European Society of Anaesthesiology and Intensive Care (ESAIC). The questionnaire consisted of 46 q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Time-controlled adaptive ventilation, compared with volume-controlled ventilation, led to less ECM damage due to better distribution of transpulmonary pressure [ 104 ]. With assisted mechanical ventilation, Neurally Adjusted Ventilatory Assist (NAVA), variable pressure support ventilation (Noisy PSV), and conventional pressure-controlled ventilation (PCV) resulted in similar lung injuries and incidence of asynchrony [ 102 ]. Noisy PSV led to lower PCIII expression than NAVA and PCV, which may be associated with different lung distribution of stress and strain.…”
Section: Effects Of Mechanical Ventilation On the Ecm In Lungs Affect...mentioning
confidence: 99%
“…Time-controlled adaptive ventilation, compared with volume-controlled ventilation, led to less ECM damage due to better distribution of transpulmonary pressure [ 104 ]. With assisted mechanical ventilation, Neurally Adjusted Ventilatory Assist (NAVA), variable pressure support ventilation (Noisy PSV), and conventional pressure-controlled ventilation (PCV) resulted in similar lung injuries and incidence of asynchrony [ 102 ]. Noisy PSV led to lower PCIII expression than NAVA and PCV, which may be associated with different lung distribution of stress and strain.…”
Section: Effects Of Mechanical Ventilation On the Ecm In Lungs Affect...mentioning
confidence: 99%
“…A survey of members of the European Society of Anaesthesiology and Intensive Care reported that only 24% of the 798 respondents knew of and followed the WHO's recommendations on perioperative oxygenation. 37 …”
Section: Routine Perioperative Oxygenation—current Anaesthetic Practicementioning
confidence: 99%
“…Hiperventilacija može skratiti ovo vreme. Preoksigenacija utiče na odlaganje arterijske desaturacije oksihemoglobina tokom perioda apneje (za vreme intubacije traheje) i produžava vreme desaturacije sa jednog minuta tokom disanja sobnog vazduha na 6,9 minuta tokom udisanja 100% kiseonika 5 . Kod pacijenata sa smanjenim kapacitetom za transport kiseonika brže dolazi do desaturacije u toku apneje.…”
Section: Primena Kiseonika Tokom Hirurškog Lečenjaunclassified